2004
DOI: 10.1291/hypres.27.47
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy Is Associated with Arterial Stiffness and Vascular Calcification in Hemodialysis Patients

Abstract: Left ventricular hypertrophy (LVH) is the most frequent cardiac abnormality in patients with end-stage renal disease (ESRD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
8
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 33 publications
6
109
8
7
Order By: Relevance
“…Elevated Ca ϫ PO 4 is a risk factor for arterial calcification (26,27). Previous studies demonstrated a potential role of PTH in promoting myocardial fibrosis (8), but our data showed no correlation between LVMI and PTH.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadcontrasting
confidence: 73%
“…Elevated Ca ϫ PO 4 is a risk factor for arterial calcification (26,27). Previous studies demonstrated a potential role of PTH in promoting myocardial fibrosis (8), but our data showed no correlation between LVMI and PTH.…”
Section: Pre-hd Bp and Ca ϫ Po 4 : Increased Afterloadcontrasting
confidence: 73%
“…There is controversy over the effect of disorders of lipid metabolism on aortic compliance. In several cross-sectional studies, lipid profile was not a determinant of PWV, 5,6,9,29 whereas serum triglyceride correlated positively with ba-PWV in hemodialysis patients 30 and increments in ba-PWV. 28 Furthermore, intermediate-density lipoprotein cholesterol, which contains cholesterol and triglyceride, was an independent risk factor for arteriosclerosis.…”
Section: Discussionmentioning
confidence: 88%
“…It has been found in several studies that pulse wave velocity correlates with the degree of left ventricular hypertrophy (20,21). Although left ventricular hypertrophy is assessed by measuring the left ventricular mass index by echocardiography, it is time-consuming to calculate the value.…”
Section: Discussionmentioning
confidence: 99%